Nationwide Impact of the 2017 American College of Cardiology/American Heart Association Blood Pressure Guidelines on Stroke Survivors. Issue 12 (19th June 2018) - Lekoubou, Alain; Bishu, Kinfe G.; Ovbiagele, Bruce
Abstract : Background: In this study, we aimed at estimating the prevalence and number of stroke survivors with hypertension, recommended pharmacological treatment, and above blood pressure target, according to the 2017 American College of Cardiology/American Heart Association guidelines and the seventh report of the Joint National Committee on prevention, detection, evaluation, and treatment of high blood pressure guidelines. Methods and Results: We included participants aged ≥20 years to the National Health and Nutrition Examination Surveys between 2003 and 2014. The National Health and Nutrition Examination Surveys is a series of publicly available, cross‐sectional, national, stratified, multistage probability surveys. The National Health and Nutrition Examination Surveys received approval from the National Center for Health Statistics Research Ethics Review Board. Stroke was determined by self‐report. Blood pressure was estimated according to National Health and Nutrition Examination Survey protocol. Assessment of pharmacological treatment of hypertension was by self‐report. The proportion and number of stroke survivors with hypertension was 49.8% (95% confidence interval [CI], 45.4%–54.2%) and 2 361 075 (95% CI, 2 035 251–2 686 899) per the 2017 American College of Cardiology/American Heart Association guidelines versus 29.9% (95% CI, 26.2%–33.7%) and 1 415 974 (95% CI, 1 191 721–1 640 227) per seventh report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure guidelines. Proportion and number of stroke survivors who were not at target blood pressure was 56% (95% CI, 51.2%–60.6%) and 1 824 106 (95% CI, 1 558 846–2 089 366) per 2017 American College of Cardiology/American Heart Association guidelines versus 36.3% (95% CI, 31.6%–41.4%) and 1 184 655 (95% CI, 984 128–1 385 182) per seventh report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure guidelines. Conclusions: Compared with seventh report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure, the 2017 American College of Cardiology/American Heart Association hypertension guidelines would result in a nearly 67% relative increase in the proportion of US stroke survivors diagnosed with hypertension and 54% relative increase in those not within the recommended blood pressure target.